ADAPTASI BERTAHAN HIDUP KELUARGA KARYAWAN YANG MENGALAMI PEMUTUSAN HUBUNGAN KERJA DARI CV. ABADI JAYA, KECAMATAN MANDAU, DURI KABUPATEN BENGKALIS - Katarina Aprillia Gultom; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Mandau Subdistrict, Duri District of Bengkalis with problem formulation that is (1) What are some forms of social adaptation conducted by households of employees experiencing Termination of Employment? (2) What is the most dominant form of Adaptation carried out by the household of the employee who is terminated? (3) What are the factors that influence employees to choose the dominant social Adaptation?Termination of employment occurred in the city of thorns, Mandau district. Termination of employment is the termination of employment relationship due to a matter that causes the ending of rights and obligations between workers and the company. The termination of employment resulted in an increase in the number of unemployed. Economically, termination of employment can stop the family income generating process, and cause difficulties in the fulfillment of life needs. In this case an adaptation strategy is needed. Adaptation strategy or survival strategy is one's ability to apply a set of ways to overcome various problems in economic life. The strategies undertaken by the five former employees are active strategy, passive strategy and network strategy. This research uses qualitative data analyst research techniques, namely the description of the actual conditions. The research subjects used are 5 employees who have experienced job termination from CV. Abadi Jaya.Keywords: termination of employment, adaptation, survival strategy.